Meningkatkan Kesehatan dan Kebersihan: Program Perbaikan Toilet di Kampung Tua Teluk Mata Ikan, Nongsa, Batam - Saputra, Ade Jaya; Ma'muriyah, Ni'matul; Meiliana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2025)
This community service project aimed to support tourism development at Teluk Mata Ikan Beach, Batam, through the renovation of public toilet facilities. The previous condition was inadequate and affected visitor comfort. The project, carried out by a team from Universitas Internasional Batam (UIB) in collaboration with PT Telin, involved site surveys, design planning, cost estimation, and construction. The result was a significantly improved facility that positively impacted visitor satisfaction and the image of the tourist area. This activity showcases collaboration between academia, industry, and the local community in addressing tourism infrastructure challenges.